Why do rates of convergence differ? A meta-regression analysis - Stephen Dobson; Carlyn Ramlogan; Eric Strobl (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2003)
There have been many tests of the convergence hypothesis yielding many different estimates of β (the speed of convergence). Narrative reviews of the convergence literature hint at possible reasons for the study-to-study variation in the value of β, but such reviews are selective and informal. In contrast, meta-regression analysis provides a more formal and objective review of the literature. It is shown that study design and methodology are important determinants of the reported convergence rate, especially in cross-national studies. There is also evidence of general misspecification in the literature.
Keywords: 330